Kebermaknaan Hidup Pada Pekerja Sosial di Unit Disabilitas Yayasan S Yogyakarta - Sri Wahyu Anggraini; Mutingatu Sholichah (Empathy : Jurnal Fakultas Psikologi, 2022)
Meaningfulness Of Life For Social Workers At Disability Unit Of S Foundation In Yogyakarta.Working as a social worker in the social sector is very challenging. The existence of various types of disabilities causes difficulties, both in adapting and communicating. Meanwhile, the financial amount received is inadequate. Research related to social workers is still limited because people are also unfamiliar with the profession of social worker. The study is a qualitative research with a phenomenological approach which aims to reveal the meaning of life of social workers at  S foundation and factors that infuence it. Data were collected through interviews and analyzed using content analysis and validated through member check technique. The manifestation of the meaning of life in social workers is reflected in the freedom of will to choose and carry out work according to their passion, without being controlled by factors outside themselves. They hold on to their choice even though their job requires them to make a lot of sacrifices without adequate financial rewards so that their families and communities perceive their job status as volunteering. Internal factors that affect the meaning of life are personality and appreciation and belief in work, while external factors consist of social support and work values.